2020
DOI: 10.1007/s40195-020-01007-1
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Balance of Strength and Corrosion Resistance in Al–Mg–Er Alloys

Abstract: High-strength, corrosion-resistant, and lightweight Al-Mg alloys perform an important function in harsh coastal service environments. Corrosion resistance is generally inversely correlated with strength; hence, it is difficult to simultaneously optimize both. In this study, a low-magnesium Er-containing Al-based alloy that is stronger and more corrosion resistant than Al-based alloys have been reported. The alloy contains Er, and the precipitation of Al 3 Er within a face-centered cubic matrix is obtained by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…However, the addition of rare earth element Erbium (Er) to the alloys purifies the alloy matrix and thus improving the corrosion resistance. Zhongjun Wang et al [35] and Haifei Zhou et al [36] confirmed that the suitable addition of Er elements enhance the corrosion resistance of magnesium alloys. Heat treatment plays a pivotal role in the corrosion resistance of magnesium alloys.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the addition of rare earth element Erbium (Er) to the alloys purifies the alloy matrix and thus improving the corrosion resistance. Zhongjun Wang et al [35] and Haifei Zhou et al [36] confirmed that the suitable addition of Er elements enhance the corrosion resistance of magnesium alloys. Heat treatment plays a pivotal role in the corrosion resistance of magnesium alloys.…”
Section: Introductionmentioning
confidence: 96%
“…The choice of the heat treatment process is supposed to accompany with specific alloy compositions and application requirements to optimize corrosion performance. However, the explanation of corrosion performance changes only focused on corrosion rate and electrochemistry in the literature [35,36]. The underlying reasons for these changes and the subsequent effects of the formed corrosion products on the corrosion behavior were not revealed deeply.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the alloy cannot be strengthened by heat treatment. Its main strengthening effect comes from strain hardening and solution strengthening [3]. One effective way to improve the mechanical properties of 5xxx aluminum alloys is solution strengthening using micro-alloying.…”
Section: Introductionmentioning
confidence: 99%
“…Adding Er and Zr into Al–Mg alloys can improve the comprehensive properties [ 11 ]. The addition of Er can form the Al 3 Er phase in the alloy, which is coherent with the Al matrix, can refine grains, pin dislocations, and improve the strength and recrystallization temperature of the alloy [ 12 ]. Adding Er and Zr into Al–Mg alloys can not only refine grains and strengthen precipitation but also form a core−shell Al 3 (Er, Zr) phase.…”
Section: Introductionmentioning
confidence: 99%